2017
DOI: 10.3389/fphar.2017.00938
|View full text |Cite
|
Sign up to set email alerts
|

Huangqi Decoction Alleviates Alpha-Naphthylisothiocyanate Induced Intrahepatic Cholestasis by Reversing Disordered Bile Acid and Glutathione Homeostasis in Mice

Abstract: Intrahepatic cholestasis is a serious symptom of liver disorders with limited therapies. In this study, we investigated the efficacy of Huangqi decoction (HQD), a two-herb classic traditional Chinese medicine (TCM), in the treatment of alpha-naphthylisothiocyanate (ANIT)-induced intrahepatic cholestasis in mice. HQD treatment ameliorated impaired hepatic function and tissue damage. A metabolomics study revealed that the endogenous metabolites significantly affected by HQD were related to bile acid (BA) biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…It has been demonstrated that several traditional Chinese medicine (TCM) remedies for treating jaundice can reverse the metabolomic fingerprint of ANIT, and therefore, protect against ANIT-induced cholestasis. These treatments include paeoniflorin (from the dried root of Paeonia lactiflora) [83,84], rhubarb [85], Yinchenhao decoction (from the above ground parts of Artemisia annua) [86], chicken bile powder (containing mainly taurochenodeoxycholic acid that is deconjugated in the gut producing the primary BA that is a FXR ligand) [87], Huangqi decoction (a TCM comprising Radix Astragali and Radix Glycyrrhizae) [88], gentiopicroside (from Gentiana rigescens Franch. ex Hemsl.)…”
Section: Cholestasismentioning
confidence: 99%
“…It has been demonstrated that several traditional Chinese medicine (TCM) remedies for treating jaundice can reverse the metabolomic fingerprint of ANIT, and therefore, protect against ANIT-induced cholestasis. These treatments include paeoniflorin (from the dried root of Paeonia lactiflora) [83,84], rhubarb [85], Yinchenhao decoction (from the above ground parts of Artemisia annua) [86], chicken bile powder (containing mainly taurochenodeoxycholic acid that is deconjugated in the gut producing the primary BA that is a FXR ligand) [87], Huangqi decoction (a TCM comprising Radix Astragali and Radix Glycyrrhizae) [88], gentiopicroside (from Gentiana rigescens Franch. ex Hemsl.)…”
Section: Cholestasismentioning
confidence: 99%
“…Metabolomics represents a powerful discipline concerned with the comprehensive analysis of small molecules to discover biomarkers in biological systems (Schrimpe-Rutledge et al, 2016;Zhang et al, 2019). This method provides holistic insights into changes in the metabolic pathways during disease or drug treatment (Wu et al, 2017;Zheng et al, 2019). Therefore, metabolomics study is in perfect accordance with the holistic approach of TCM, and can provide clues to mechanism of action of TCM (Wu et al, 2017;Zheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…α-Naphthylisothiocyanate (ANIT) is a substance usually used to start cholestasis by harming epithelial cells of the bile conduits and causing serious cholangitis and intrahepatic cholestasis (Yan et al, 2017;Wu et al, 2017;Han et al 2018). A one of a kind treatment of rats explored different avenues regarding αnaphthylisothiocyanate (ANIT) which can harm the liver with intrahepatic cholestasis (Plaa and Clerical, 1976;Kossor et al, 1993;Golbar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…ANIT instruments with cholestasis have been proposed; however, it has not yet been completely explained. It has been prescribed that lessened hepatic glutathione (GSH) be added to the movement of hepatic inclusion related with ANIT-prompted cholestasis because of its capacity to deliver a reversible ANIT-S conjugate which is basic for the vehicle of ANIT into the bile where it is discharged at high fixations and most likely lethal (Roth and Dahm, 1997;Yan et al, 2017;Wu et al, 2017). Likewise, it has been proposed that neutrophil-intervened aggravation might be added to the enhancement of ANIT-initiated cholestatic liver damage in rats (Roth and Dahm, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation